2008
DOI: 10.1111/j.1551-2916.2008.02343.x
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of ZrB2 Powder During Wet Processing – Analysis and Control

Abstract: Corrosion behavior of ZrB 2 powder during wet processing in water or ethyl alcohol was studied both with and without an organic additive. Incorporation of oxygen and pH change did not intensively occur during static aging of aqueous slurries, but corrosion was enhanced when stirring the slurries. The oxygen content of the powder increased rather rapidly with milling time in ethyl alcohol. The molecular weight of polyethylenimine effected the pH change and oxygen content of ZrB 2 powder, after corrosion in wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“… ZrB 2 and SiC are the main components; Si 3 N 4 is the sintering aid; B 2 O 3 , ZrO 2 , and SiO 2 are originally present in the raw powders and also formed on the particles surfaces during the wet milling; 21 and carbon is a raw powder impurity and further carbon sources are the polyethylene bottles used during ball milling, binder, and sintering atmosphere; 6,22,23 many reactions occurred during sintering, changing the final composition and forming new phases. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… ZrB 2 and SiC are the main components; Si 3 N 4 is the sintering aid; B 2 O 3 , ZrO 2 , and SiO 2 are originally present in the raw powders and also formed on the particles surfaces during the wet milling; 21 and carbon is a raw powder impurity and further carbon sources are the polyethylene bottles used during ball milling, binder, and sintering atmosphere; 6,22,23 many reactions occurred during sintering, changing the final composition and forming new phases. …”
Section: Resultsmentioning
confidence: 99%
“…B 2 O 3 , ZrO 2 , and SiO 2 are originally present in the raw powders and also formed on the particles surfaces during the wet milling; 21 and…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, the melt powder was washed several times by hot distilled water until no F -was detected in the washing solution by AgNO 3 . The obtained powder was subjected to acid leaching, using a dilute HCl solution to remove the aluminium and residual salts in consideration with ZrB 2 particles have no reaction with HCl [21]. The leached mass was washed repeatedly with hot distilled water until it was free of Cl - [22].…”
Section: -Experimental Proceduresmentioning
confidence: 99%
“…Unfortunately, when preparing aqueous ZrB 2 nanosuspension, nanoparticles easily form agglomerates owing to the large surface area and high surface energy. Research by a number of authors has just shown their interests in the dispersion behavior of ZrB 2 micrometer‐ and submicrometer‐sized powders in aqueous solution . Zhang et al .…”
Section: Introductionmentioning
confidence: 99%